Effects of cover crops on soil hydraulic properties during commodity crop growing season. (1st April 2022) - Haruna, Samuel I.; Ritchey, Edwin; Mosley, Chaney; Ku, Seockmo
Abstract: Cover crops (CCs) can improve soil hydraulic properties prior to termination, but their effects on soil hydraulic properties during the growing season are less known. The objective of this study was to investigate the influence of no‐till CC on the soil hydraulic properties during the commodity crop growing season in Murfreesboro, USA. The CCs included hairy vetch ( Vicia villosa Roth.), crimson clover ( Trifolium incarnatum L.), winter wheat ( Triticum aestivum L.), winter peas ( Lathyrus hirsutus L.), oats ( Avena sativa ), triticale ( Triticale hexaploide Lart.), barley ( Hordeum vulgare L.) and flax ( Linum usitatissimum L.). The cash crop grown was corn ( Zea mays ). Soil samples were collected using a cylindrical core (55 mm inside diameter, 60 mm long) at 0–10, 10–20, and 20–30 cm depths during April (prior to CC termination), May, June and July. Results showed that soil bulk density (Db) was 23%, 12%, 11% and 10% higher under no cover crop (NCC) compared with CC management during April – July, respectively. This suggests a lower rate of soil consolidation under CC management even after several rainfall events. Four months after CC termination, macroporosity and total porosity were 306 and 50% higher, respectively, under CC compared with NCC management. Therefore, saturated hydraulic conductivity ( K sat ) during July was two times higher under CC management compared with NCC management and this can affect increase water infiltration and conservation during the growing season. Due to CC root‐induced improvement in macroporosity, CCs had 64% higher volumetric water content (θ) at saturation during July compared with NCC management. Cover crops can improve soil hydraulic properties and these benefits can persist for up to four months after termination.